Multifunctional Roles of Plant Dehydrins in Response to Environmental Stresses - Liu, Yang; Song, Qiping; Li, Daxing; Yang, Xinghong; Li, Dequan (Frontiers in Plant Science, 2017)
To respond to abiotic stresses, plants have developed complex mechanisms that allow them to rapidly perceive and respond to environmental changes. Late embryogenesis abundant (LEA) proteins are a diverse and large family that play important roles in environmental stress tolerance in plants. Dehydrins belong to group II LEA proteins, which are considered stress proteins involved in the formation of plants’ protective reactions to dehydration. Some studies have demonstrated that dehydrins could binding metal ions or lipid vesicles. In vitro experiments revealed that dehydrins could protect the activity of enzyme from damage caused by environmental stress. Although many studies have been conducted to understand their roles in abiotic stresses, the molecular function of dehydrins is still unclear. In this review, to generate new ideas for elucidating dehydrins’ functions, we highlight the functional characteristics of dehydrins to understand their roles under environmental stress in plants.